Herding Cats – Future Professionals' Expectations of Attractive Employers. (May 2015) - Bullinger, Bernadette; Treisch, Corinna
Professionals, like business consultants, have been described as crucial for modern knowledge-intensive organizations, but they are not always thought to be easy to manage or to attract. This might be due to a need for autonomy and commitment that is aimed more at the profession than at their employer. For their recruitment it is thus important for modern organizations like professional service firms (PSFs) to know what expectations applicants who are future professionals have regarding human resource (HR) principles and programmes. We refer to the institutional logics perspective to gain insights whether, in the context of PSFs, applicants' expectations are associated with the logic of the profession, the corporation or the family. This article describes a discrete choice experiment conducted to analyse the influence of HR attributes in job advertisements used by PSFs to attract business management students. We use a hierarchical Bayesian analysis to carry out the conjoint analysis, as it enabled us to measure the relative importance of attributes on an individual level. The results show that first required job-related attitudes and then company and job description are the most important features of a job advertisement. Our study also indicates that future professionals simultaneously draw on different institutional logics when deciding which employer is attractive.